DISTORSI GAYA HIDUP DARI PERSPEKTIF TEOLOGIS SEBAGAI IDE DALAM PENCIPTAAN KARYA SENI LUKIS - Sihombing, Richard Rogate; Gulendra, I Wayan; Budiarta, I Dewa Putu Gede (Program Studi Seni Murni ISI Bali, 2025)
ABSTRACT TThis final report describes the process of creating a painting with the theme “Lifestyle Distortion from a Theological Perspective”. This theme focuses on the deterioration of the human lifestyle that is getting worse and has a negative impact on individuals and the environment. The Bible, as the holy book of Christianity, is used as inspiration and a benchmark to compare today's lifestyle, which is often enjoyed by many people despite its destructive potential. Through this artwork, it is hoped that viewers can see a reflection of these lifestyle deviations, trigger self-reflection, and inspire them to live a better and more meaningful life. A total of six artworks were produced using various techniques and media, with the application of the elements and principles of fine art. Each work depicts the distortion of human lifestyles that are increasingly far from theological teachings. This visualization is designed to show the negative impact of lifestyle changes that are not in accordance with spiritual values, so that viewers can better understand the dangers posed. The aim of this work is to provide insight and inspiration for individuals to evaluate their chosen lifestyle and encourage change towards a more ethical life that is in line with theological principles.